Prevalence of cyberbullying among students in Malaysian higher learning institutions - Lai, C.S.; Mohamad, M. M.; Lee, M.F.; Mohd Salleh, K.; Sulaiman, N.L.; Rosli, D.I.; Chang, W.V.S. (American Scientific Publishers, 2017)
This research was conducted to gain an understanding of the prevalence of cyberbullying among students in Malaysian higher learning institutions. Additionally, the present research also attempted to find out the common platforms where cyberbullying occurs and coping strategies used by cyber victims. A set of questionnaire was developed for the purpose of data collection. A total of 712 public and private college/university students participated in this research. The research findings revealed that 66% of the respondents reported having been cyberbullied; the prevalence rate for female was higher compared to male cyber users; Malays students yielded highest percentage of cyber victims compared to other ethnic groups. Current findings also indicated that Facebook and mobile phone social apps were the most common platforms where cyberbullying took place. The exploration of cyberbullying effects showed that most of the cyber victims became over sensitive towards their surrounding and developed emotional changes. Apart from that, the findings also indicated that the most common coping strategy was seeking assistance from friends and classmates. Pragmatic and effective steps have to be taken by higher leaning institutions in order to help students deal with problems in cyberbullying and more importantly to prevent cyberbullying from happening.